Applying Pulse Width Modulation in Body Coupled Communication - Miltiadis Moralis-Pegios; Pelagia Alexandridou; Christos Koukourlis (Journal of Electrical and Computer Engineering)
We study the application of Pulse Width Modulation (PWM) technique in Body Coupled Communication. The term Body Coupled Communication is used in order to specify that the human body or a part of it, such as an arm, is used as a path that transfers digital information. The digital information is either generated due to coupling of the body, for example, in medical equipment as a result of a measurement, or generated by external circuitry attached somewhere onto the body and is transferred to a terminal by touching it. In this paper, the latter case will be described, where, for illustration purposes, the touch of the human hand on a doorknob triggers the unlocking mechanism.